PEMBENTUKAN KARAKTER RELIGIUS SISWA MELALUI PROGAM BACA TULIS AL-QUR’AN (BTQ) DI SD NEGERI 2 BALEDONO - William Jasson Ngangi; Mukh Nursikin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The decline in religious character has a negative impact on students. The formation of religious character through the BTQ (Baca Tulis Al-Qur'an) program is both a supporting and hindering factor. The BTQ program plays a role in achieving students' religious character. This study uses a qualitative phenomenological method. Data was obtained through observation, interviews, and documentation. Data analysis was conducted by reducing, presenting, and drawing conclusions. The results of the study show that the formation of religious character is carried out by classifying BTQ classes and implementing several programs that support BTQ. Supporting factors of the BTQ program include educators accompanying students, student motivation, and the school's vision and mission. Hindering factors include educator tardiness and absenteeism, lack of student motivation, and reduced general lesson hours. Achievements in religious character through the BTQ program include reading and revising the Qur'an after prayer, arriving at school on time, being polite, and obeying parents and educators. The implications of this study show that educational practitioners, teachers, parents, and education managers can understand that religious character can be created and shaped through the Baca Tulis Al-Qur'an program.